Quranic Moral in Pancasila: Efforts to Strengthen Mental Revolution Through the First Principle of Pancasila - Shodiq, Muhammad (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2021)
This research aimed to reveal that the values contained in Pancasila were relevant to the values contained in the Al-Qur’an. Al-Qur’an morals that were relevant to the Pancasila mentality were worthy of being the guide and strengthening of the mental revolution in Indonesia This study was a library research using a social and political psychological approach. The primary data were the verses of morality in the Al-Qur’an and the points of Pancasila; while the secondary data were Al-Mi>za>n by Thaba'thaba'i, and Al-Ja>mi 'li Ahka>m al-Qura>n by al-Qurtubi > and some literature relevant to this research. This study found that the concept of one and only Godhead in the first principle of Pancasila was the concept of tawhid governing another four principles. Besides mental revolution was the application of Pancasila morals that was in harmony with the Al-Qur’an so that the Indonesian people could arouse their tawhid passion in all aspects of life. Believing in God Almighty steadily gave birth to obedience, loyalty and obedience to all His commandments. Implementing all religious teachings formed a humane society that was just and civilized, united in Indonesian unity, by prioritizing the attitude of deliberation, in realizing fair social justice in various forms in the fields of economy, politics, law and education. This research concluded that the mental revolution of Pancasila should be within the mental framework of the One and Only Godhead.",